2014
DOI: 10.1371/journal.pone.0085095
|View full text |Cite
|
Sign up to set email alerts
|

Physical Weight Loading Induces Expression of Tryptophan Hydroxylase 2 in the Brain Stem

Abstract: Sustaining brain serotonin is essential in mental health. Physical activities can attenuate mental problems by enhancing serotonin signaling. However, such activity is not always possible in disabled individuals or patients with dementia. Knee loading, a form of physical activity, has been found to mimic effects of voluntary exercise. Focusing on serotonergic signaling, we addressed a question: Does local mechanical loading to the skeleton elevate expression of tryptophan hydroxylase 2 (tph2) that is a rate-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The group led by Yokota, on another side, used a commercial knee electro-mechanical loading system (ElectroForce 3100, Bose Corporation, Eden Praire, MN, USA) which applies lateral loads to the knee to induce anabolic responses in the skeleton [ 60 , 61 ] to study the effects of this treatment in rat brains [ 42 ]. The rationale behind their hypothesis derived from the observation that physical activities, regularly involving application of a mechanical load on the skeleton, seem to have a stimulatory role in pain control, neural regeneration and synthesis of neurotransmitters [ 43 , 62 , 63 ].…”
Section: Molecular Determinants Of Mt: Lessons From Animal Models mentioning
confidence: 99%
See 1 more Smart Citation
“…The group led by Yokota, on another side, used a commercial knee electro-mechanical loading system (ElectroForce 3100, Bose Corporation, Eden Praire, MN, USA) which applies lateral loads to the knee to induce anabolic responses in the skeleton [ 60 , 61 ] to study the effects of this treatment in rat brains [ 42 ]. The rationale behind their hypothesis derived from the observation that physical activities, regularly involving application of a mechanical load on the skeleton, seem to have a stimulatory role in pain control, neural regeneration and synthesis of neurotransmitters [ 43 , 62 , 63 ].…”
Section: Molecular Determinants Of Mt: Lessons From Animal Models mentioning
confidence: 99%
“…The rationale behind their hypothesis derived from the observation that physical activities, regularly involving application of a mechanical load on the skeleton, seem to have a stimulatory role in pain control, neural regeneration and synthesis of neurotransmitters [ 43 , 62 , 63 ]. The authors show that by using RT-qPCR, western-blot and immunohistochemistry analysis, that knee loading of 1 N at 5Hz for 1500 cycles and a 5 min treadmill running (positive control) upregulated messenger RNA (mRNA) levels of tryptophan hydroxylase 2 ( Tph 2) in the raphe nuclei of brain stem, the site of serotonin synthesis in the brain, in reference to sham load and 90 min tail suspension (stressed negative control) [ 42 ]. In addition, these authors showed that the mRNAs encoding two transcription factors of the Tph 2 gene ( Sim 1 and Pet 1) were significantly upregulated by this knee-loading treatment as well [ 43 ].…”
Section: Molecular Determinants Of Mt: Lessons From Animal Models mentioning
confidence: 99%
“…The group led by Yokota, on another side, used a commercial knee electro-mechanical loading system (ElectroForce 3100, Bose Corporation, Eden Praire, MN) which applies lateral loads to the knee to induce anabolic responses in the skeleton [55,56] to study the effects of this treatment in rat brains [57]. The rationale behind their hypothesis derived from the observation that physical activities, regularly involving application of a mechanical load on the skeleton, seem to have a stimulatory role in pain control, neural regeneration and synthesis of neurotransmitters [58][59][60].…”
Section: Neuroimmune Impact Of Mtmentioning
confidence: 99%
“…The rationale behind their hypothesis derived from the observation that physical activities, regularly involving application of a mechanical load on the skeleton, seem to have a stimulatory role in pain control, neural regeneration and synthesis of neurotransmitters [58][59][60]. The authors show by using RT-qPCR, western-blot and immunohistochemistry analysis, that knee loading of 1 N at 5Hz for 1500 cycles and a 5 minute treadmill running (positive control) upregulated mRNA levels of tryptophan hydroxylase 2 (tph2) in the raphe nuclei of brain stem, the site of serotonin synthesis in the brain, in reference to sham load and 90 minute tail suspension (stressed negative control) [57]. In addition, these authors showed that the mRNAs encoding two transcription factors of the Tph2 gene (Sim1 and Pet1) were significantly upregulated by this knee-loading treatment as well [58].…”
Section: Neuroimmune Impact Of Mtmentioning
confidence: 99%
“…9 It is also reported that knee loading can activate neuronal signaling and elevate the serotonin level in the brain. 10 We have previously shown that ankle loading, the other form of joint loading modality, ameliorated tumor-driven bone loss by inhibiting the nuclear factor of activated T-cells cytoplasmic 1 (NFATc1)-driven bone resorption in the loaded tibia. 11 However, little is known about loading effects on systemic metabolites or tumorigenesis that is not directly linked to bone homeostasis.…”
Section: Introductionmentioning
confidence: 99%